The tapestry of culture [ an introduction to cultural anthropology - Rosman, Abraham; Rubel, Paula G.; Weisgrau, Maxine K. (AltaMira Press, 2009)
The Oral History Manual grounds oral historians in the practice of oral history, taking the reader through the entire process, from the idea for a project through the completed, archived interviews.